Effects of Various Dietary Patterns on Total Cholesterol, Triglycerides, HDL, and LDL in Male Wistar Rats - Mulyani, Yani; Kaniawati, Marita; Fajeri, Nur Iman (International Journal of Health, Medicine, and Sports, 2025)
Atherosclerosis is a cardiovascular disorder characterized by lipid plaque buildup in arterial walls. Lipid profile is a critical factor in the risk of developing atherosclerosis and is strongly influenced by dietary patterns. This study aimed to investigate the effects of ketogenic, ketofastosis, and high-fat–high-carbohydrate (HFHC) diets on the lipid profile—including total cholesterol, triglycerides, HDL, and LDL—compared to a standard diet in male Wistar rats. Male Wistar rats were divided into four dietary groups: standard, ketogenic, ketofastosis, and HFHC. Each group was fed its respective diet for 30 days. On day 31, lipid profile parameters were measured using an automatic analyzer (COBAS C-311®), and body weight was also recorded. No significant differences were found in body weight or total cholesterol among the groups (p > 0.05). Both ketogenic and ketofastosis diets reduced triglyceride levels, with only the ketofastosis group showing a statistically significant reduction (p < 0.05). The HFHC diet increased triglyceride levels, though not significantly (p > 0.05). All three experimental diets significantly increased HDL levels (p < 0.05), with the ketofastosis diet showing the greatest effect. Additionally, all three diets significantly decreased LDL levels (p < 0.05). Ketogenic, ketofastosis, and HFHC diets positively affected lipid profiles by improving HDL and reducing LDL levels in Wistar rats. Among these, the ketofastosis diet demonstrated the most favorable lipid-modulating effects.